The Development of a University Recycle Management System (ReMaS): The Experience of UPSI - Modi Lakulu; Azniah Ismail (Pejabat Karang Mengarang UPSI, 2014)
The main aim of this study is to design and develop a recycling management system called ReMaS. An efficient recycling management system is important in assisting related activities in order to protect the environment, and furthermore, it also helps to educate the community, especially in universities, in practicing recycling activities in their daily lives. The development of this system is not only timely but necessary in view of the low awareness about recycling among many sections of the Malaysian community. ReMaS was built based on the prototype approach and was then appraised through a survey, in particular, to measure the system usability and user interface. The findings revealed that all the respondents agreed that the multimedia elements used in the system were appropriate and the system itself was easy to use. Thus, through a user friendly, easy to use recycling management system such as ReMaS, eﬀorts to inculcate a high level of empathy toward keeping our environment clean and safe will be better facilitated. Overall, this study provides some useful insights in developing such a system that can pull in all parties to work together more efficiently in carrying out recycling activities in order to help preserve our environment.